Challenges in School library management: an exploratory study based on Island Zone of Jaffna District - Thirumaran, S.; Navaneethakrishnan, S. (Sri Lanka Library Association, 2015)
Efficiency in school library administration depends on the challenges ahead of the school librarian in the present millennium. School Libraries were developed to support an activity based curriculum, and to encourage the reading habit in school environment. They can play a key role in school-wide information management. In Sri Lanka school libraries have generally been managed by teacher librarians or teacher in charge for library, under the direct supervision of the principals of the respective schools. Among the five educational zones of Jaffna district, Island zone have more difficult areas which is covered by Velanai, Kayts and Delft divisions. Altogether fifty schools with 7546 students are functioning in this zone under the Ministry of Education. Objective of this paper is to identify the complex nature of challenges in library management with particular reference to school libraries in Island Zone of Jaffna district. To determine management challenges this study employs quantitative research method. Twenty five schools from Island Zone were chosen for this study using random sampling method on the basis of their location and the grade. Self-administered questionnaires were distributed to the principals and teacher-librarians separately to ensure reliability of the responses. Only one school failed to response. This study illustrates the following core categories of challenges faced by school libraries. Insufficient collection and resources in the library, threats of book enemies and disasters, problems in housekeeping operations due to the lack of policies, unavailability of specific space and side in a healthy condition, inappropriate furniture and library equipments, inadequate service due to the lack of trained library professionals, reducing budgets and limited financial support, irregular user education programmes and unavailability of ICT facilities were identified as major constrains of these libraries. It is realized that recognition by school management of the potential of the library service could encourage the progression and development of the service. School libraries have to address the needs of students’ communities, support for and use of the library service. Further it is also recommended that well equipped and functional school libraries are indispensable to support and enhance the quality and standard of teaching and learning in schools of this zone.
Keywords: Library Management; Education; School libraries